THE EFFECT USAGE OF CRYOPROTECTIVE TYPES ON THE QUALITY OF SURIMI FISH SIAMESE (Pangasius hypophthalmus) - Syaiful Irzal; N. Ira Sari; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research aimed to determine usage effect of types cryoprotective on the surimi quality of fish siamese. The method used in this research is the conduct the surimi making of fish siamese with the addition of different cryoprotective. The cryoprotective ingredients used in this research is the S0 = (sucrose 4% + polyphosphate 0,3%), S1 = (sorbitol 4% + polyphosphate 0,3%), S2 = (sucrose 4% + 4% sorbitol + polyphosphates 0, 3%). Parameters tested were physical analysis consists of fold test, bite test and chemical analysis consists of moisture content and protein content. The average value surimi of fish siamese with the addition of cryoprotective ingredients S0, S1 and S2 respectively for fold test was 4,63, 4,81, 6,33, bite test 5,11, 5,00, 5,35, moisture content 68.19%, 70.26%, 71.63%, and the protein content of 9.27%, 11.70%, 13.26%. The results showed that surimi of fish siamese with the addition of cryoprotective on the treatment S2 is the best treatment. The value of folding test, bite test, moisture and protein content of surimi are 6.33, 5.35, 71.63% and 13.26%.Key word: surimi, fish siamese, types of cryoprotektive